Legal Education and the Public Interest - Andrew Goldsmith (Legal Education Review)
Law is both powerful and pervasive. It is also, for the most part, highly public in nature. The social settings in which legal considerations arise are virtually endless. The number of ordinary citizens affected by legal problems on a daily basis far exceeds the number of those who go to court or consult lawyers about such matters, or even those who may seek to discover their legal position through a visit to a library, a legal advice service, or the Internet. In a democratic society, some knowledge of the law is a highly desirable commodity. It provides consciousness of entitlements to benefits and protections and also provides ways of organising and structuring a variety of personal and business transactions. Legal knowledge can therefore play both a protective and facilitative role. This redistributive potential of legal knowledge raises questions about the conceptions, philosophies and structures of legal education in our society. What should count as legal knowledge, and how access to legal knowledge is determined, are profoundly political questions. As with most political questions, the interests at stake are not simply defined by the self-interest of a few individuals or well-entrenched groups. The range of people affected by law means that the stakeholders in legal education in a democratic society cannot be narrowly limited. While there are some obvious traditional sectional and private interests involved, the public interest in legal education is easily forgotten or ignored. It is precisely this question that concerns me here.